An Experience with Simulation Modelling for Radial Flow Pump - Al-Khalid, Hj Othman; Mohd Azlan, Ismail; Hushairi, Zen (SRYAHWA Publications, 2015)
The aim of this paper is to present the simulation modelling process of an end suction centrifugal pump using commercial Computational Fluid Dynamics software. The study pump is a radial flow pump with specific speed of 1075.0 (mm/mm). Three distinct models, called Volute, Impeller and Draft Tube, were generated based on the geometry and dimension of the pump. Unstructured tetrahedral mesh were applied to all flow domains, utilizing the advantage of good meshing capability for complex surface geometries. The governing equations that were used are steady-state three-dimensional Navier-Stokes equations coupled with the k-epsilon turbulence model. It can be observed that the simulation result yield comparable performance when compared with the manufacturer data sheet. Pressure distribution, velocity vector and velocity streamline visualization show local losses inside the pump. It is believed that the finding from this study complement the ongoing research relevant to turbomachinery modelling and will be useful to investigate hydraulic characteristic inside the pump.